Self-efficacy perceived in academic behaviors in university students of ‘health’ and ‘social’ sciences - López Walle, Jeanette M.; Rangel Ledezma, Yunuen; Blanco Vega, Humberto; Rodríguez Villalobos, Judith Margarita; Castillo Fernández, Isabel María (2015)
The aim of this present study consisted in comparing the profiles of the academic Self-efficacy perceived in ‘Social’ and ‘Health’ Sciences University students. The total sample was 1113 subjects; 524 from Health Sciences and 589 from Social Sciences, with an average age of 18.20 years (DS= 0.72) and 18.24 years (DS=0.74) respectively. The approach adopted in this research was framed into a quantitative approach with a descriptive design, survey type. The results show that the perceived self-efficacy profiles are very similar among ‘Social’ and ‘Health’ Sciences students. And behaviors related to ‘Communication’ factor, represent an opportunity area for University students in their first year. Future studies should replicate these findings with larger samples.